Gene cloning and expression analysis based on primary culture of fin cells from Centropyge vrolikii - Dingyuan Luo; Ning Xi; Shengkai Shi; Yizhen Lu; Zebin Chen; Hongwei Liu; Jincan Chen; Hai Huang; Zhaowei Zhong; Yonghua Jiang (Journal of Fish Biology, 2026)
Skin coloration is a distinctive phenotype and an economically important trait in ornamental fish. Understanding its regulatory mechanisms is crucial for both aquaculture and selective breeding. In this study, we cloned and analysed the full‐length complementary DNA (cDNA) sequences of four key pigmentation‐related genes— mitf , mc1r , tyr and sox10 —in the black‐tailed angelfish ( Centropyge vrolikii ). We established the fin‐derived tissue cell line of C. vrolikii (CVFTCL) and confirmed its transfection efficiency using EGFP, achieving 40%–50% expression 24 h post‐transfection, providing an in vitro platform for subsequent gene function verification. Using the primary fin cell culture system, we conducted overexpression and RNA interference (RNAi) experiments to investigate the regulatory relationships among these genes. Overexpression of mitf upregulated mc1r but downregulated sox10 and tyr ; overexpression of mc1r enhanced mitf expression while inhibiting sox10 and tyr ; overexpression of tyr only increased tyrp1 expression and overexpression of sox10 upregulated both mc1r and mitf , without affecting tyr . RNAi‐mediated knockdown confirmed the efficiency of gene silencing and supported the regulatory relationships inferred from overexpression experiments. Collectively, these findings indicate that mitf , mc1r , tyr and sox10 may interact to coregulate melanocyte development and melanin synthesis, thereby influencing skin coloration in C. vrolikii . This study provides a mechanistic framework for pigmentation regulation and a foundation for colour improvement and selective breeding in this species.